2001
DOI: 10.1124/mol.60.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Stimulation of p42/p44 Mitogen-Activated Protein Kinase in PC12 Cells: Role of Gi/o, G Protein-Coupled Receptor Kinase 2, β-Arrestin I, and Endocytic Processing

Abstract: In this study, we have shown that nerve growth factor (NGF)-dependent activation of the p42/p44 mitogen-activated protein kinase (p42/p44 MAPK) pathway in PC12 cells can be partially blocked by pertussis toxin (which inactivates the G proteins G(i/o)). This suggests that the Trk A receptor may use a G protein-coupled receptor pathway to signal to p42/p44 MAPK. This was supported by data showing that the NGF-dependent activation of p42/p44 MAPK is potentiated in cells transfected with G protein-coupled receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 19 publications
3
59
1
Order By: Relevance
“…The increased potency of L-AP4 in inhibiting adenylyl cyclase activity in cells overexpressing GRK2 is consistent with this hypothesis. These results are different from those obtained in HEK293 cells expressing the mGlu1 receptor or in PC12 cells, where GRK2 enhances the stimulation of MAPK by quisqualate and NGF, respectively (Iacovelli et al, 2003;Rakhit et al, 2001). This excludes that GRK2 has a nonspecific effect on the MAPK pathway and suggests that the enzyme affects the early steps of mGlu4 receptor signaling.…”
Section: Discussioncontrasting
confidence: 54%
“…The increased potency of L-AP4 in inhibiting adenylyl cyclase activity in cells overexpressing GRK2 is consistent with this hypothesis. These results are different from those obtained in HEK293 cells expressing the mGlu1 receptor or in PC12 cells, where GRK2 enhances the stimulation of MAPK by quisqualate and NGF, respectively (Iacovelli et al, 2003;Rakhit et al, 2001). This excludes that GRK2 has a nonspecific effect on the MAPK pathway and suggests that the enzyme affects the early steps of mGlu4 receptor signaling.…”
Section: Discussioncontrasting
confidence: 54%
“…The observations presented here document the only known trigger for redistribution of A2 and p11 to the HUVEC exterior and provide insight into the mechanism since thrombin induces signaling through G proteins. Like thrombin, the effects of nicotine and nerve growth factor (Rakhit et al, 2001) domains (Sagot et al, 1997); (2) A2 has been identified as a component of caveolae (Stahlhut et al, 2000;Harder and Gerke, 1994;Stan et al, 1997); (3) cell-surface A2 has been colocalized with caveolin (van der Goot, 1997); and (4) nerve growth factor induces exposure of A2 on the neurite surface (Jacovina et al, 2001), we propose that A2 transport to the cell surface may involve G-protein-linked control of caveolae.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained activation of ERK1/2 leads to neurite outgrowth and the development of phenotypic characteristics in PC12 cells (Kao et al, 2001;Rakhit et al, 2001). However, the mechanisms that link the activation of NGF receptors to neuritogenesis are not welldefined.…”
Section: Introductionmentioning
confidence: 99%